Surto de mastite bovina causada por Arcanobacterium pyogenes - Motta, Rodrigo Garcia [UNESP]; Ribeiro, Márcio Garcia [UNESP]; Perrotti, I. B. M. [UNESP]; Motta, D. G. [UNESP]; Domingues, Paulo Francisco [UNESP]; Lucas, T. M. [UNESP]; Zamprogna, T. O. [UNESP]; Listoni, F. J. P. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2011)
An uncommon outbreak of mastitis caused by Arcanobacterium pyogenes in 26 cows is reported. The epidemiological findings, clinical signs, microbiological exams, somatic cell count, in vitro susceptibility profile of strains, efficacy of intramammary treatment and control measures were discussed. Florfenicol (96.2%), cefoperazona (92.3%), cefaloxin (84.6%) and ceftiofur (84.6%) were the most effective antimicrobials, and neomicin (27.0%) and enrofloxacin (17.4%) the least effective antimicrobials.
Outbreak of bovine mastitis caused by Arcanobacterium pyogenes
Keywords: dairy cattle; Arcanobacterium pyogenes; outbreak; mastitis